New insights into the mechanism of graphene oxide and radionuclide interaction. (March 2020) - Kuzenkova, Anastasiia S.; Romanchuk, Anna Yu; Trigub, Alexander L.; Maslakov, Konstantin I.; Egorov, Alexander V.; Amidani, Lucia; Kittrell, Carter; Kvashnina, Kristina O.; Tour, James M.; Talyzin, Alexandr V.; Kalmykov, Stepan N.
Abstract: The sorption of U(VI), Am(III)/Eu(III) and Cs(I) radionuclides by graphene oxides (GOs) synthesized by Hummers's, Brodie's and Tour's methods was studied through a combination of batch experiments with characterization by microscopic and spectroscopic techniques such as X-ray photoelectron spectroscopy (XPS), attenuated total reflection fourier-transform infrared spectroscopy (ATR-FTIR), high-energy resolution fluorescence detected X-Ray absorption spectroscopy (HERFD-XANES), extended X-ray absorption fine structure (EXAFS) and high resolution transmission electron microscopy (HRTEM). Remarkably different sorption capacity and affinity of radionuclides was found towards GOs synthesized by Hummers's and Brodie's methods reflecting different structure and oxidation state of these materials. Mechanism underlying GO – radionuclide interaction is determined using variety of experimental techniques. For the first time it is shown here that GO - radionuclides interaction takes place on the small holes or vacancy defects in the GO sheets. Mechanism of GO's interaction with radionuclides was analyzed and specific functional groups responsible for this interaction were identified. Therefore, a new strategy to produce improved materials with high capacity for radionuclides suggests the use perforated and highly defected GO with a larger proportion of carboxylic functional groups. Graphical abstract: Image 1